1997
DOI: 10.1080/01635589709514576
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 suppresses growth and expression of albumin gene in a human hepatoma cell line HepG2

Abstract: The effect of vitamin B6 on the growth of a human hepatoma cell line HepG2 in culture was studied. The growth of HepG2 cells and protein synthesis were almost completely inhibited in medium supplemented with 5 mM pyridoxine. Pyridoxal was as effective as pyridoxine, but pyridoxamine showed no inhibitory action. The growth inhibition of HepG2 cells by pyridoxine was accompanied by a marked inhibition of secretion of plasma proteins, particularly albumin. Northern blot analysis of albumin mRNA showed that pyrido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The Lu and PN ligands (despite PN is active against the hepatoma cell line HepG2 [26], the human pancreatic carcinoma cell line PANC-1 [27] and the feline mammary tumour cell line FRM [28]) showed a low activity and, as in other cases [29], the activities of the complexes decreased as the size of the R substituent decreased; the Me and Et derivatives had a low activity that made determination of the IC 50 value unwarranted.…”
Section: In Vitro Antitumor Screeningmentioning
confidence: 95%
“…The Lu and PN ligands (despite PN is active against the hepatoma cell line HepG2 [26], the human pancreatic carcinoma cell line PANC-1 [27] and the feline mammary tumour cell line FRM [28]) showed a low activity and, as in other cases [29], the activities of the complexes decreased as the size of the R substituent decreased; the Me and Et derivatives had a low activity that made determination of the IC 50 value unwarranted.…”
Section: In Vitro Antitumor Screeningmentioning
confidence: 95%
“…Analyses of PN supplementation in cancer animal models (azoxymethane-induced colon tumorigenesis and 7,12-dimethylbenzanthracene-induced mammary tumorigenesis) revealed that high-dose PN prevented tumor progression ( 14 , 15 ). In human hepatoma HepG2 cells ( 16 ) or feline mammary tumor FRM cells ( 17 ), highdose B 6 was found to inhibit cell growth and induce apoptosis. However, the mechanism of the antitumor effects of B 6 has not yet been elucidated.…”
mentioning
confidence: 99%
“…3) On the other hand, Molina and co-workers showed that growth of HepG2 cells, a human hepatoma cell line, was severely inhibited by the addition of high levels of pyridoxine (PN) to a culture medium, and growth inhibition was accompanied by a marked inhibition of expression of the albumin gene. 4) More recent studies have shown that dietary supplementation with vitamin B 6 markedly suppressed azoxymethane-induced colon carcinogenesis in mice by reducing cell proliferation. 5) Thus supraphysiological doses of vitamin B 6 appear to reduce tumor cell growth.…”
mentioning
confidence: 99%